2018
DOI: 10.3390/jrfm11020024
|View full text |Cite
|
Sign up to set email alerts
|

Credit Ratings and Liquidity Risk for the Optimization of Debt Maturity Structure

Abstract: The purpose of this study is to examine the relationship between credit rating scales and debt maturity choices. A liquidity hypothesis is used to formulate the testable proposition and conceptual framework. Generalized linear model (GLM) and pooled ordinary least square (OLS) are utilized by SAS programming to test the proposed hypothesis. Other different estimation techniques are also used for robust evidence. Results suggest that companies with high and low ratings have a shorter debt maturity. Companies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Shortterm borrowings have relatively short terms, while longterm investments have longer terms to generate returns, putting companies under enormous cash fow pressure. Relevant studies have found that the higher the proportion of short-term borrowings in the total assets of the company, the greater the risk of the enterprise's stock price crash and the greater the liquidity risk when the enterprise's borrowings are repaid [16]. Te short-term loans of enterprises will signifcantly afect the asset quality and proftability of enterprises, resulting in an imbalance in the fnancing structure of enterprises and increasing the risk of enterprises falling into a fnancial crisis [17,18].…”
Section: Sundown Industrymentioning
confidence: 99%
“…Shortterm borrowings have relatively short terms, while longterm investments have longer terms to generate returns, putting companies under enormous cash fow pressure. Relevant studies have found that the higher the proportion of short-term borrowings in the total assets of the company, the greater the risk of the enterprise's stock price crash and the greater the liquidity risk when the enterprise's borrowings are repaid [16]. Te short-term loans of enterprises will signifcantly afect the asset quality and proftability of enterprises, resulting in an imbalance in the fnancing structure of enterprises and increasing the risk of enterprises falling into a fnancial crisis [17,18].…”
Section: Sundown Industrymentioning
confidence: 99%
“…Credit Rating Agencies (CRAs) play a crucial role in the financial markets by providing independent assessments of borrowers' creditworthiness (Rowe, 2020), (Xiaodie & Cai, 2020). Investors, lenders, and other market participants use these assessments to measure the risk associated with investing or lending to a particular entity (Sajjad & Zakaria, 2018), (Xiaodie & Cai, 2020). Rating agencies give useful and credible information about performance and creditworthiness of companies, which aids in reducing information asymmetry between lenders and borrowers (Machek & Hnilica, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their influence is derived from the rating they produce is utilized by investors and market participants to make informed decisions (Machek & Hnilica, 2013), (Xiaodie & Cai, 2020). These agencies not only assess the creditworthiness of entities but also have an impact on financial market regulation (Sajjad & Zakaria, 2018). With the rise of international credit markets, the importance of credit rating agencies has increased dramatically (Machek & Hnilica, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that older apartments with just one room are more likely to experience risk reduction benefits in the context of a housing portfolio. Sajjad and Zakaria (2018) examine the relationship between credit rating scales and debt maturity choices using a sample of non-financial listed Asian companies rated by Standard and Poor's rating agency. The non-financial companies are chosen from eight selected Asian regions: Japan, South Korea, Singapore, China, Hong Kong, Indonesia, Malaysia, and India.…”
mentioning
confidence: 99%